Growth Inhibitory Activity of Selected Australian Syzygium Species against Malodour Forming Bacteria - Wood, Aiden Joshua; McManus, Kane; Wright, Mitchell Henry; Greene, Anthony Carlson; Cock, Ian Edwin (Pharmacognosy Communications)
Background: Extracts produced from S. australe and S. luehmannii fruit and leaves are potent growth inhibitors of many bacterial pathogens. They may also inhibit the growth of malodour producing bacteria and thus be useful deodorant components, although this is yet to be tested. Methods: S. australe and S. luehmannii fruit and leaf solvent extracts were investi- gated by disc diffusion assays against significant bacterial contributors to axillary and plantar malodour formation. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: S. australe and S. luehmannii solvent extracts were good inhibitors of B. linens and C. jeikeium growth, with zones of inhibition up to 10 mm measured. S. australe extracts were generally better inhibitors of both bacterial species compared with the S. luehmannii extracts. Ethyl acetate extracts were particularly potent, with MIC values of 300 and 857 µg/mL for the S. australe fruit and leaf extracts respectively against B. linens, and 1000 and 311 µg/mL against C. jeikeium. The S. luehmannii fruit ethyl acetate extracts were similarly potent growth inhibitors, with MIC values of 571 and 203 µg/mL against B. linens and C. jeikeium respectively. S. australe aqueous and methanolic leaf extracts were also potent inhibitors of C. jeikeium (MIC’s of 285 and 306 µg/mL respectively). All other extracts had moderate or low inhibitory activity. All of the most potent ethyl acetate extracts were nontoxic in the Artemia franciscana bioassay. In contrast, the methanolic and aqueous S. australe leaf extracts, as well as the aqueous and methanolic S. luehmannii fruit extracts displayed apparent toxicity. However, these results may be fallacious and instead result from the high antioxidant content of these extracts. Conclusion: The potent growth inhibition of axillary and plantar malodour producing bacteria by the Syzygium spp. extracts indicate their potential as deodorant components.
Keywords: Body odour; Deodorant; Corynebacterium; Myrtaceae; Riberry; Brush cherry; High antioxidant; Medicinal plants